Direct Probing of Polarization Charge at Nanoscale Level. Issue 1 (14th November 2017) - Kwon, Owoong; Seol, Daehee; Lee, Dongkyu; Han, Hee; Lindfors‐Vrejoiu, Ionela; Lee, Woo; Jesse, Stephen; Lee, Ho Nyung; Kalinin, Sergei V.; Alexe, Marin; Kim, Yunseok
Abstract: Ferroelectric materials possess spontaneous polarization that can be used for multiple applications. Owing to a long‐term development of reducing the sizes of devices, the preparation of ferroelectric materials and devices is entering the nanometer‐scale regime. Accordingly, to evaluate the ferroelectricity, there is a need to investigate the polarization charge at the nanoscale. Nonetheless, it is generally accepted that the detection of polarization charges using a conventional conductive atomic force microscopy (CAFM) without a top electrode is not feasible because the nanometer‐scale radius of an atomic force microscopy (AFM) tip yields a very low signal‐to‐noise ratio. However, the detection is unrelated to the radius of an AFM tip and, in fact, a matter of the switched area. In this work, the direct probing of the polarization charge at the nanoscale is demonstrated using the positive‐up‐negative‐down method based on the conventional CAFM approach without additional corrections or circuits to reduce the parasitic capacitance. The polarization charge densities of 73.7 and 119.0 µC cm −2 are successfully probed in ferroelectric nanocapacitors and thin films, respectively. The obtained results show the feasibility of the evaluation of polarization charge at the nanoscale and provide a new guideline for evaluating the ferroelectricity at the nanoscale. Abstract : The evaluation of polarization charge at the nanoscale is of great interest, but it is hard to acquire polarization charge due to the low signal‐to‐noise ratio. However, the polarization charge can be obtained by applying the positive‐up–negative‐down method to the conventional conductive atomic force microscopy system without any other circuits. Through this method, polarization charge can be evaluated at the nanoscale.